Examination of thermophysical characteristics of food products - Zinaida Burova; Serhii Ivanov; T. Roman; Volodymyr Vasyliv; Mariia Zheplinska; Mikhailo Mushtruk; Ihor Palamarchuk; Viktor Sarana; Maksym Hudzenko (Тваринництво та технології харчових продуктів, 2021)
The development of food, biotechnological, and processing industries, the invention of new ingredients, optimisation and improvement of technological processes require reliable information about the main thermophysical characteristics of raw materials and materials of biological origin. This paper presents the results of the cooperation of specialists from leading universities and scientific institutions of Ukraine, embodied in the developed methods of analysing the parameters of thermodynamic and mass transfer processes and determining the thermophysical characteristics of the latest substances and products using modern metrologically certified devices and information-measurement systems. The main problem in analysing materials of biological origin is the inhomogeneity and heterogeneity of the structure of samples. It is demonstrated that it is advisable to determine the coefficient of effective thermal conductivity of bulk materials and cereals in a stationary thermal mode on a device for determining the thermophysical characteristics of materials and thermal effects, equipped with heat flow and temperature sensors, in which a symmetric scheme of the thermometric measurement method is implemented. The simultaneous use of four measuring cells allows for performing a synchronous comparative analysis of several samples, and the rotary-clamping mechanism helps to minimise contact resistances. The developed method of measuring the coefficient of effective thermal conductivity considers the features of bulk food products and substantially improves the accuracy of the examination by introducing a correction for the contact resistance of the wall layer. Long-term observations allow for analysing thermolabile materials, examining thermal effects in samples, and evaluating volumetric and integral heat generation. It is necessary to use the STA system to conduct calorimetric studies of a wide range of biological materials and substances with the necessary accuracy, which implements methods of step-by-step scanning and synchronous thermal analysis to determine the specific heat capacity, the heat of evaporation, and the ratio of free and bound moisture in nonhomogenous materials. These characteristics are necessary parameters for analysing the kinetics and optimisation of heat and mass transfer processes, in particular, drying, in the calculation and design of technological equipment